Supermicrosurgical lymphatic venous anastomosis for intractable lymphocele after great saphenous vein harvesting graft - Hirofumi Imai, MD; Shuhei Yoshida, MD, PhD; Toshiro Mese, MD; Solji Roh, MD; Isao Koshima, MD, PhD (Journal of Vascular Surgery Cases and Innovative Techniques, 2022)
Lymphoceles result from either trauma to the lymphatic vessels or after vein graft harvest, which occurs in 10% to 16% of patients. When a lymphocele persists despite conservative treatment, patients can experience undue distress. We have reported the case of successful treatment using lymphatic venous anastomosis (LVA) of an intractable lymphocele that had been refractory to conservative treatment, including stretch bandaging, drainage, and local injection for 2 years after great saphenous vein harvest. The lymphocele resolved shortly after the LVA without any adverse effects. LVA can be a useful and minimally invasive alternative treatment of lymphocele after harvesting the great saphenous vein.